Possible Weight Regain Managements after Bariatric Surgery - Mona Kamali Ardekani; Vivienne A. Lacy; Sahar Eshghjoo; Taha Anbara (Ожирение и метаболизм, 2022)
Obesity is an uprising trend across the world resulting in huge costs for healthcare systems and declines in the quality of life in patients. Bariatric surgery is one of the most effective approaches to weight loss. Although bariatric surgery can be considered as a minimally invasive approach it has a series of complications such as weight regain 1 to 4 years after surgery. Nonetheless, most patients achieve sufficient weight loss, but the other subjects with supervised strategies would be able to manage food intake and change problematic lifestyles to continue the weight loss process. In this review article, we aim to gather valuable interventions performed and reported by researchers to manage weight regain in bariatric patients. Weight regain is a multi-factorial condition owing to hormonal imbalances, nutritional deficiencies, physical inactivity, mental health disorders, problematic dietary behaviors, medical issues such as thyroid, adrenal, kidney, or heart problems, taking new medications, diabetes relapse, and pregnancy, as well as anatomic and surgical factors. Therefore, its remission needs interdisciplinary approaches.